Risk factors for endometriotic-cyst associated ovarian cancer: A case controlled study - Pannueng Udomsinkul; Surang Triratanachart; Shina Oranratanaphan (Elsevier, 2020)
Objective: Primary objective is to identify risk factors of endometriotic-cyst associated ovarian cancer (EAOC). Secondary objective is to evaluate the clinical characteristics of EAOC patients. Materials and Methods: A retrospective case-control study was conducted by analyzing data of patients from 1999 to 2014. Cases were endometriotic-cyst associated ovarian cancer with pathologically confirmed diagnosis. Controls were randomly selected with year-matched patients with benign ovarian endometriotic cyst. Univariate and multivariate with logistic regression analyses were used to identify patients' characteristics that were risk factors for endometriotic-cyst associated ovarian cancer. Results: Altogether, 158 controls and 79 EAOC cases were recruited. Mean age of the EAOC group was 13 years older than that of the control group (49 vs. 36 years). The most common stage of EAOC was stage I (59.74%). Clear cell subtype is the most commonly found in this population (60.76%). Univariate analysis showed that age ≥42 years, menopause, weight loss, cyst diameter ≥8.33 cm, presence of solid area, bilaterality and CA 125 higher than 117.6 units/ml were significant. Multivariate analysis showed that patients with age ≥42 years (OR 7.69, 95%CI: 2.47, 23.87), menopause (OR 33.19, 95%CI: 2.37, 465.12), weight loss (OR 11.94, 95%CI: 1.52, 94.08), cyst diameter ≥ 8.3 cm (OR 10.56, 95%CI: 4.39, 25.35) and presence of solid area by ultrasonography (OR 6.70, 95%CI: 2.19, 22.35) were significant risk factors for EAOC. Conclusion: Advanced age, menopause, weight loss, cyst diameter ≥ 8.33 cm and presence of solid area from ultrasonography were important risk factors for EAOC. Keywords: Endometriotic cyst, Endometriotic-cyst associated ovarian cancer (EAOC), Multivariate analysis, Ovarian cancer, Risk factor